Four new C19-diterpenoid alkaloids from Aconitum hemsleyanum var. circinatum. Issue 9 (2nd September 2019) - He, Dan; Liu, Wang-Yan; Xiong, Jiao; Xu, Jun-Ju; Shen, Yong
Abstract: Four new C19-diterpenoid alkaloids, hemaconitines A–D (1 –4 ), were isolated from the roots of Aconitum hemsleyanum var. circinatum. Their structures were elucidated as 19R-hydroxyl-secoyunnaconitine (1 ), (3R)-hydroxyl-liwaconitine (2 ), 14-anisoyl-leucanthumsine E (3 ), and 19R -acetonyl-8-O-methyltalatisamine (4 ) by extensive spectroscopic analysis (IR, UV, HR-ESI-MS, 1D, and 2D NMR). Graphical Abstract: